Sensitivity of Cerebrospinal Fluid Cytology for the Diagnosis of Cryptococcal Infections: A 21-Year Single-Institution Retrospective Review. Issue 2 (15th October 2018) - McHugh, Kelsey E; Gersey, Melanie; Rhoads, Daniel D; Procop, Gary W; Zhang, Yaxia; Booth, Christine N; Sturgis, Charles D
Abstract: Objectives: Cryptococcal meningoencephalitis is the most common fungal infection of the central nervous system diagnosed by cerebrospinal fluid cytology (CSF) studies. Existing literature suggests that routine CSF cytomorphologic evaluations are exquisitely specific; however, less is known about their sensitivity. Methods: An electronic record review of the cytopathology and microbiology files was conducted for the 21-year interval from January 1, 1995, through December 31, 2015. Results: In 21 years, 12, 584 CSF samples were processed in the laboratory. Of these, 24 (0.2%) were reported positive for cryptococcal organisms by light microscopy, and 129 CSF fungal cultures were positive for Cryptococcus species. All cotested specimens with positive cytology results were positive on culture (15 specimens, 100% specificity). Twenty-four samples with positive culture results were negative by CSF cytology (sensitivity 39%). Conclusions: When culture is used as a gold standard, CSF cytology is 100% specific and 39% sensitive, with a positive predictive value of 100% and a negative predictive value of 99.8%.